Research into surface properties of disperse fillers based on plant raw materials - Danchenko, Yuliya; Andronov, Vladimir; Kariev, Artem; Lebedev, Vladimir; Rybka, Evgeniy; Meleshchenko, Ruslan; Yavorska, Dayana (Eastern-European Journal of Enterprise Technologies, 2017)
The properties of the dispersed fillers are investigated based on the agricultural and wood industry wastes: buckwheat and oats husk, wood and pineneedle flour. We experimentally determined structuralrheological characteristics, morphology and acidbase properties of the surface. By applying a potentiometric determining of hydrogen indicator of aqueous suspensions рНsusp., we studied the qualitative and quantitative characteristics of acidbase active centers on the surface of the particles of fillers. It was revealed that the surface of buckwheat husk is dominated by two types of active centers: weaklyacidic (рKа≈5.53–5.83) and close to neutral (рKа≈6.16–6.30). The surfaces of wood flour and pineneedle flour are characterized as the weaklyacidic with centers рKа≈5.29–5.52 and рKа≈5.02–5.36, respectively. Based on sources from the scientific literature, we compiled a comparative characteristic of the chemical composition of the examined fillers. A correlation is established between chemical composition, physicalchemical and surface properties. It is shown that the total mass content of cellulose and lignin can be one of the criteria for evaluating resistance of the fillers to high temperatures and acidicbase properties. A decrease in the sum of mass content of cellulose and lignin in the composition of fillers results in the improved thermal resistance while the surface acidity decreases. The results obtained allow us to predict behaviour of the fillers in compositions and control performance characteristics of composite materials.